Enhancing assessment in learning management systems: The efficacy of AI tools in electronic test design - Mohammed, Mohammed Ahmed Elhossiny; Al-Aosail, Abdulaziz Bin Faleh; Lamouchi, Ali; Abdellatif, Mohamed Sayed (Research Journal in Advanced Humanities, 2025)
Learning Management Systems (LMS) play a crucial role in contemporary education because they allow online learning experiences and evaluations. The subject of this study is the efficacy of incorporating AI technologies into the design process of electronic tests inside LMS systems. This research hoped to shed light on optimizing assessment processes in online learning settings by investigating how AI-driven methods affect assessment quality and results. This research uses a mixed-methods strategy, analyzing the quantitative and qualitative aspects of test performance and user experiences. The results show that using AI to construct tests improves the efficiency, flexibility, and student involvement of assessments inside learning management systems. However, things like algorithmic bias and consumer acceptability are still quite significant. We suggest better using AI in designing electronic tests on LMS systems.